Emotion and reasoning in human decision-making - Edmund T. Rolls (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
Two systems in the brain that are involved in emotional and economic decision-making are described. The first is an evolutionarily old emotion-based system that operates on rewards defined by the genes such as food, warmth, social reputation, and having children. Such decisions are often based on heuristics, such as being highly sensitive to losses, because a single loss might influence one's reproductive success. This is a multidimensional system with many rewards and punishers, all of which cannot be simultaneously optimized. The second route to decision-making involves reasoning, in which it is assumed that utility can be accurately assessed and logical reason can be applied, though the human brain is not naturally computationally good at logical assessment. When decisions are taken, all those factors apply, and in addition there is noise introduced into the system by the random firing times of neurons for a given mean firing rate. The implications for economic decision-making are described. In macroeconomics, it is assumed that the economy behaves like one 'representative' agent who can take rational and logical decisions, and who can maximize utility over a constraint. Given the neuroscience of decision-making, the situation is more complex. The utility function may be multidimensional, the reward value along each dimension may fluctuate, the reasoning may be imperfect, and the decision-making process is subject to noise in the brain, making it somewhat random from occasion to occasion. Moreover, each individual has a different set of value functions along each dimension, with different sensitivities to different rewards and punishers, which are expressed in the different personalities of different individuals. These factors underlying the neuroscience of human decision-making need to be taken into account in building and utilizing macroeconomic theories.
Keywords: D01; D87; D91; E71; G41; 330; decision-making; brain mechanisms; probabilistic choice; attractor network; reward value; economic value; macroeconomics; microeconomics; orbitofrontal cortex